Analisis Kompetensi Guru Biologi SMA Se-Kabupaten Batu Bara - Rahmadani, Fitri; Harahap, Fauziyah; Edi, Syahmi (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
The objective of this research was to observe the pedagogic, professional, personal, and social competence of high school biology teachers in Batu Bara district. The population in this research were all of biology teacher in high school of Batu Bara district as many 22 people. Samples were taken by purposive sampling with a sample of 22 teachers, 90 students from 9 schools were each taken 10 students, 3 lecturers as validator expert. This research was conducted by using descriptive qualitative. Data were collected using questionnaire of observation, test comprehension, student assessment, teacher and student questionnaires. The results showed that pedagogic competence was appropriate, with the highest result in the mastery of the learning (4,85Â±0,357) and pre-learning (4,32Â±0,862) but still in appropriate criteria, from the test given to teachers on average 57,72 % of teachers can answer the test given by the highest score successfully answered 39 questions with 78% comprehension level of the lowest value just answer 11 questions with a level of comprehension 22%.In the professional competence of the teaching materials scored significantly higher values ââ(116.05 Â± 6.973) and the lowest value (38.91 Â± 3.350) suggesting that teacher professional attitude towards the teaching materials they provide.The results of a questionnaire assessment of teachers and students questionnaire also showed the results of personal competence and social competence biology teacher in Batu Bara District was very well.At the personal competence, the average value of the total aspects of the assesment (77.68 Â± 5.867) and assessment of students with an average value (89.77 Â± 4.350), and on the social competence, the mean value of the total aspects of the assessment (85.09 Â± 3.829 ) on the teacher questionnaire, as well as the mean value (87.53 Â± 3.706) in the student questionnaire.This study has implications for the importance of sustainable development for high school biology teachers in Batu Bara district.